2020
DOI: 10.3390/ani10091690
|View full text |Cite
|
Sign up to set email alerts
|

Review: Application and Prospective Discussion of Machine Learning for the Management of Dairy Farms

Abstract: Dairy farmers use herd management systems, behavioral sensors, feeding lists, breeding schedules, and health records to document herd characteristics. Consequently, large amounts of dairy data are becoming available. However, a lack of data integration makes it difficult for farmers to analyze the data on their dairy farm, which indicates that these data are currently not being used to their full potential. Hence, multiple issues in dairy farming such as low longevity, poor performance, and health issues remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 100 publications
(175 reference statements)
0
39
0
1
Order By: Relevance
“…Applied statistical methods used in the literature [ 16 ] showed that milking frequency, lactation number (parity number), month of milking, and type of lying stall represent important factors responsible for the monthly milk yield of dairy cows in farms with AMSs. In this context, Machine Learning (ML) algorithms have been already applied in some areas of dairy research, particularly to predict data, and they represent a promising tool, useful to develop and improve decision support for farmers [ 17 ] in order to increase both milk yield and animal welfare and, on the other hand, to reduce the resources needed, hence increasing the sustainability of the sector [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applied statistical methods used in the literature [ 16 ] showed that milking frequency, lactation number (parity number), month of milking, and type of lying stall represent important factors responsible for the monthly milk yield of dairy cows in farms with AMSs. In this context, Machine Learning (ML) algorithms have been already applied in some areas of dairy research, particularly to predict data, and they represent a promising tool, useful to develop and improve decision support for farmers [ 17 ] in order to increase both milk yield and animal welfare and, on the other hand, to reduce the resources needed, hence increasing the sustainability of the sector [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms offer new approaches for the analysis of large amount of data collected in dairy farming thanks to the use of herd management systems 25 and milk testing performed in the frame of national recording procedures. Machine learning methods are indeed a promising tool to improve decision support systems for farmers and have already been applied in different areas of dairy research such as behaviour, feeding, management, physiology and reproduction 25 . Such advanced analyses allow to predict outcomes of economic relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of published studies on ML methods applied to animal science, a reliable practical implementation of most tested algorithms for management decision has not occurred yet. This may be due to the availability of poor training data 25 . To improve prediction accuracies, data retrieved from many different herds and recorded for longer time periods should be considered, and large integrated high-quality datasets have to be created.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we find that chopped straw as litter in free-stalls for lactating cows (OR=1. 26 Environmental conditions play a secondary role in the prediction of periparturient hypocalcemia. The association of a high standard deviation of temperature with increased risk of periparturient hypocalcemia (OR=1.48 [1.34; 1.63] is consistent with a similar finding in the literature 91 .…”
Section: /30mentioning
confidence: 99%
“…Several machine learning (ML) approaches have been considered for the prediction of breeding values 15 , insemination success 16 , feed intake 17 and calving 18 , as well as milk yield [19][20][21] , modelling of physiological and behavioural animal parameters 22,23 and estimating BCS 24,25 -see also Cockburn 2020 26 for a recent review. The literature on the prediction of diseases is frequently based on black-box sensor systems in which prediction algorithms are used that are of commercial interest and not publicly known or evaluated 26 or the reported sensitivity and specificity of prediction algorithms varies widely 9 . Diseases for which successful applications of ML approaches have been reported include lameness [27][28][29] , mastitis [30][31][32][33] , metabolic status, i.e.…”
Section: Introductionmentioning
confidence: 99%